2004
DOI: 10.1128/iai.72.8.4637-4646.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mucosally DeliveredSalmonellaLive Vector Vaccines Elicit Potent Immune Responses against a Foreign Antigen in Neonatal Mice Born to Naive and Immune Mothers

Abstract: The development of effective vaccines for neonates and very young infants has been impaired by their weak, short-lived, and Th-2 biased responses and by maternal antibodies that interfere with vaccine take. We investigated the ability of Salmonella enterica serovars Typhi and Typhimurium to mucosally deliver tetanus toxin fragment C (Frag C) as a model antigen in neonatal mice. We hypothesize that Salmonella, by stimulating innate immunity (contributing to adjuvant effects) and inducing Th-1 cytokines, can enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Single cell suspension from spleens was prepared as previously described (30). To harvest BM cells, skin-peeled hind legs were removed and the bone cavity of femurs and tibiae were flushed with 3-5 ml of complete RPMI medium; cells centrifuged and resuspended in complete medium.…”
Section: Igg Ab-secreting Cells (Asc)mentioning
confidence: 99%
See 3 more Smart Citations
“…Single cell suspension from spleens was prepared as previously described (30). To harvest BM cells, skin-peeled hind legs were removed and the bone cavity of femurs and tibiae were flushed with 3-5 ml of complete RPMI medium; cells centrifuged and resuspended in complete medium.…”
Section: Igg Ab-secreting Cells (Asc)mentioning
confidence: 99%
“…To harvest BM cells, skin-peeled hind legs were removed and the bone cavity of femurs and tibiae were flushed with 3-5 ml of complete RPMI medium; cells centrifuged and resuspended in complete medium. The frequency of IgG ASC were measured as previously described (30). Briefly, microtiter plates were coated with 5 g/ml MV lysate, washed with PBS, and blocked with complete medium.…”
Section: Igg Ab-secreting Cells (Asc)mentioning
confidence: 99%
See 2 more Smart Citations
“…19 The presence of antigen-specifi c antibodies in the mucosa may be due to local production by antibody-secreting cells (IgA) or through transudation of circulating immunoglobulin from the sera (IgG or IgA). In general, mucosal IgG is thought to be transudative, 20 although Gockel et al 21 showed local production of IgG after topical administration of There are clear advantages to using noninvasive vaccine delivery methods. Since many immunizations in the past were s.c., the boost injections could be avoided by i.n.…”
Section: Resultsmentioning
confidence: 99%